The RxPinoy health directory. (Infomediary Philippines, 2002)
It has names and contact numbers of Metro Manila-based physicians and allied health professionals arranged in its specialty index. It also contains a list of Metro Manila hospitals and health centers. It also contains an index of Filipino surgeons on the net.